EXOGENOUS OXYTOCIN IMPAIRS CAUDAL EPIDIDYMAL SPERM CHARACTERISTICS IN SPRAGUE-DAWLEY RATS - Yama OE; Odetola AA; Okoko IE; Kusemiju TO; Lukpata PE (Ntec Specialist, 2018)
Background: Oxytocin is a neuropeptide hormone that is released from posterior pituitary gland and has been shown to increase cervical contractions, modulates sperm production, transport and ejaculation. Objectives: This study aimed at determining the effect of exogenous oxytocin on caudal epididymal sperm characteristics in Sprague-Dawley rats. Method: Forty adult male Sprague-Dawley rats weighing between 180-300 g were randomly distributed into 4 groups A, B, C and D of 10 rats each. Group A served as the control group while groups B to D were the treated groups. Oxytocin was administered intramuscularly to groups B, C and D at the doses of 1 IU/kg/body weight(b.w.), 2 IU/kg/b.w. and 3 IU/kg/b.w. two days of three days interval per week respectively while 0.5ml of 0.9% physiologic saline was administered to group A. The treatment was carried out for a period of 8 weeks. Results: The result showed a significant increase in the mean caudal epididymal sperm volume among the groups that received 2 IU/kg/b.w. and 3 IU/kg/b.w. C and D at 4weeks and 8weeks when compared with control (p less than 0.05). The caudal epididymal sperm concentration of the treated groups showed a significant decrease compared to the control at 4 and 8 weeks (p less than 0.001). Groups that were administered with 2 IU/kg/b.w. and 3 IU/kg/b.w. oxytocin showed a significant decrease in sperm concentration compared to control and the lowest dose oxytocin treated group (p less than 0.001) at 8weeks. Conclusion: Chronic intramuscular administration of oxytocin has significant deleterious effect on caudal epididymal sperm concentration